Rebranding Produk Krecek Keripik Gadung pada UMKM Kota Kediri - Mufidatul Jariyah; Tamara Nur Budiarti; Aprilia Dhia Ghina; Geovania Nage Nuwa (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
MSME companies that have been in operation for decades are now expected to be able to compete and expand alongside one another, given the large number of new MSME enterprises that are beginning to be founded. Because there are so many products on the market with similar quality and composition, MSMEs must have a unique selling point to set their products apart from the competition. Using the Community Partnership Program (PKM) to create MSME logos is a wise move to modernize MSMEs' identities and enable them to effectively convey who and what they now stand for. As part of this program, MSMEs that have been in business for a long time are chosen for this activity, which is conducted from observation to the logo printing procedure. It also gives the target market a positive, consistent, and impressive image of MSME entities and products, which will increase the product's selling value and attractiveness. Finally, it presents an eye-catching and educational logo that is suitable for all levels of society.